Reversible heart failure: the role of inflammatory activation. Issue 1024 (19th November 2010) - Robinson, Tim; Smith, Alyson; Channer, Kevin S
Abstract : Heart failure is increasingly common in western populations and is an inevitable consequence of the improved survival after myocardial infarction, and of an ageing population. Heart failure is usually relentlessly progressive as the maladaptive processes triggered by the physiological changes of the condition lead to further deterioration. However, in certain circumstances, heart failure is transient or potentially reversible when it occurs as part of intense systemic inflammatory activation. This review considers the role of inflammation in the aetiology of heart failure, and illustrates the strategies which have been used to modify the inflammatory response with anonymised clinical case reports.